Stroke in young adults: A 3-month outcome analysis and predictors of mortality in Northeast India – A regional perspective - Baiakmenlang Synmon; Iada Rilang Tiewsoh; Tamajyoti Ghosh; SR Sharma; C Daniella; Nasheman Khongthaw; Pynjanai Thongni (Asian Journal of Medical Sciences, 2025)
Background: Stroke in young adults (18–50 years) is a growing public health challenge, with Northeast India reports a disproportionately high incidence (36.7% of total strokes). This study analyzes functional outcomes and mortality predictors using the modified Rankin scale in young stroke patients.